Efectos colaterales de los anticonceptivos orales e inyectables utilizados por las Servidoras del Gobierno Provincial de Loja. - Quizhpe Puglla, Diana Esthefania (2013)
The purpose of this study was to determine the side effects of oral and injectable contraceptives submitted by users Loja Provincial Government, in order to determine the female populations currently use contraception and to establish what types of contraceptives used each of them. 82 surveys were conducted to the servants in their respective area of work, with the presence of the physician responsible for the organization, who agreed under its responsibility, the information obtained was essential for the proposed study. It was found that the servants of GPL using contraception most 51 % , of which 36% presented using injectable side effects such as absence of bleeding 38 % , 24 % weight gain , mood disturbances 19 % , headache 14 % , increased bleeding 5% and 33% who used oral contraceptives had headache 38 % , 33 % weight gain , mood disturbances 21 %, no bleeding and increased 4% each . With the information found taking delivery of a triptych and talks to promote the necessary information on the use of hormonal contraceptives and their possible side effects. KEYWORDS: Oral contraceptives, injectables, side effects.